(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of depression in under graduate students of Medical Colleges. Study Design: Descriptive cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Psychiatry, Gajju Khan Medical College Swabi Pakistan from May 2018 to November 2018. Materials and Methods: Two hundred and fifty medical students, 50 from each class were randomly selected for this descriptive cross section study. The students were first assessed for the presence of depression using the International Classification of Diseases 10 criteria. Those who were found to have symptoms of depression were then evaluated for the severity of depression using Beck's Depression Inventory. Results: The mean age was 20.97±1.58 years. The mean Beck’s Depression Inventory score was 19.60±11.37. The lowest score on Beck’s Depression Inventory was 2 while the highest Beck’s Depression Inventory score was 52. There were 67 (26.80%) males and 183 (73.20%) females. Depression was found in 93 (37.20%) study participants. When depression was cross-tabulated against history of substance abuse and residence of study participants, P value was found <0.05. Conclusion: There is a high prevalence of depression among medical students and it is significantly associated with history of substance abuse and residence.